STAKEHOLDERS MAPPING DALAM UPAYA PENCEGAHAN STUNTING KABUPATEN BENGKULU SELATAN - Daru Bailovan, Kevin; Warsono, Hardi; Sunu Astuti, Retno (Journal of Public Policy and Management Review, 2024)
This research focuses on stakeholder mapping in the efforts to prevent stunting in Bengkulu Selatan Regency. Stunting is a serious global health problem, including in Indonesia, with high prevalence in rural areas. This study aims to identify the stakeholders involved in stunting prevention efforts in Bengkulu Selatan Regency, their respective roles, as well as the driving and inhibiting factors in their involvement. The method used is descriptive qualitative research with relevant supporting data. The results of the study indicate that there are four main groups of stakeholders involved, namely local government (Bappeda, Health Office, Population Control and Family Planning Office, Women's Empowerment and Child Protection Office, and Food Security Office), community (Wahana Visi Indonesia and posyandu cadres), academia (Midwifery Academy of Bengkulu Selatan), and mass media (Radar Selatan). These stakeholders are classified into primary, key, and supporting/secondary stakeholders. The local government plays the role of key player in stunting prevention efforts, while the community and academia act as subjects contributing to program implementation in the field. The mass media plays a supporting role in disseminating information and raising public awareness. The main driving factors for the success of the stunting prevention program include supportive policies and positive values in the community. Conversely, the inhibiting factors identified are the lack of effective communication and low levels of trust among stakeholders. This research provides a better understanding of the importance of cross-sector collaboration in stunting prevention efforts and highlights the need for improved communication and increased trust to achieve more optimal results.